2020
DOI: 10.3390/ijms21239143
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Ovarian Cancer Cell Growth by AT-MSC Microvesicles

Abstract: Transport of bioactive cargo of microvesicles (MVs) into target cells can affect their fate and behavior and change their microenvironment. We assessed the effect of MVs derived from human immortalized mesenchymal stem cells of adipose tissue-origin (HATMSC2-MVs) on the biological activity of the ovarian cancer cell lines ES-2 (clear cell carcinoma) and OAW-42 (cystadenocarcinoma). The HATMSC2-MVs were characterized using dynamic light scattering (DLS), transmission electron microscopy, and flow cytometry. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
(54 reference statements)
2
11
0
Order By: Relevance
“…In this document, these three components originated from this mesenchymal source could stimulate the apoptosis process and attenuate the proliferation, viability, and colony formation in OC cells in vitro (Figure 3). 86 These positive influences of AD‐MSCs on OC were also supported by other authors 87,88 . It seems that AD‐MSCs can have a dual role against OC depending on the heterogeneity of the MSCs population and the strategy of use.…”
Section: Adipose Tissue Mscs and Ocsupporting
confidence: 54%
“…In this document, these three components originated from this mesenchymal source could stimulate the apoptosis process and attenuate the proliferation, viability, and colony formation in OC cells in vitro (Figure 3). 86 These positive influences of AD‐MSCs on OC were also supported by other authors 87,88 . It seems that AD‐MSCs can have a dual role against OC depending on the heterogeneity of the MSCs population and the strategy of use.…”
Section: Adipose Tissue Mscs and Ocsupporting
confidence: 54%
“…In our laboratory, the positive effect of MVs produced by the HATMSC1 line and the HEPC.CB1 endothelial stem cell line on the formation of the endothelial cell network was demonstrated [ 46 ]. In contrast, the MVs produced by our second line, HATMSC2, showed a cytotoxic effect on ES-2 ovarian cancer cells and especially OAW-42 [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This miRNA-mediated mechanism increased pro-apoptotic molecules (BAX, CASP9, and CASP3), whereas decreased the levels of the anti-apoptotic protein BCL2 [62]. ADSC-secreted microvesicles from immortalized ADSCs demonstrated the capacity to induce pro-apoptotic and necrotic effects in two ovarian cancer cell lines, in vitro [73]. The administration of ADSC-derived microvesicles determined a dramatic reduction in the tumor cell secretion of pro-tumorigenic cytokines, such as IL-6, IL-8, GRO-alpha, and VEGF.…”
Section: Ev-mediated Antitumor Effects and Possible Therapeutic Strategiesmentioning
confidence: 95%
“…As discussed above, the relationship between ADSCs and ovarian cancer seems to have mainly tumor-promoting effects. Nonetheless, some authors have also demonstrated a possible tumor-inhibiting role of ADSCs and their EVs [10,62,72,73]. Omental ADSCs, from both metastatic and non-metastatic patients, could reduce the proliferation of A2780 ovarian cancer cell lines in vitro [10].…”
Section: Ev-mediated Antitumor Effects and Possible Therapeutic Strategiesmentioning
confidence: 99%